The effect of a permanent saltwater barrier on Rangia cuneata, an indicator species of brackish conditions. (30th September 2020) - Christensen, Ana B.; Pyne, Matthew I.
Abstract: Rangia cuneata is a brackish water clam with a broad distribution along western Atlantic coasts and is an important component of estuarine communities. Adult R. cuneata are tolerant of salinities ranging from 0 to 32 but limited experimental studies have indicated that spawning and larval development are constrained to salinities between 2 and 10. In 2003, a permanent saltwater barrier was built in the lower Neches River, Texas, that partitioned a population of R. cuneata that had been surveyed since the 1950s. The barrier prevented salt water intrusions upstream and provided a natural experiment to determine how the regulation of salinity intrusion can influence R. cuneata spawning, recruitment, and establishment. We surveyed a total of 12 historical sites (eight above and four below the barrier) plus one site outside the previous surveys. Above the barrier, five sites had no living R. cuneata and the remaining three sites had very low densities (<0.2 per m −2 ). The large sizes of the few R. cuneata above the barrier (mean = 65.8 mm) suggested no spawning, with energy instead being invested into somatic growth. It also demonstrated the effectiveness of the barrier in preventing the continued recruitment of R. cuneata upstream and supports the hypothesis that non-zero salinity levels are needed for successful reproduction of the species. Populations downstream from the barrier experienced a resurgence in population size since the last survey in 1992, with one site having >86 individuals m −2 . The presence of distinct size cohorts indicated that spawning and recruitment occurs sporadically. Using the results of previous research, we defined the conditions apparently needed for successful reproductive events as warm weather periods with a salinity change (≥4 over a week) to induce spawning and elevated salinity levels (2–10 for 15+ days) for larval development. Using these criteria, we identified three salinity influx events on the lower Neches River in the last eight years that correlate with the presence of the size cohorts observed below the barrier, which support the hypothesis that salinity fluxes and durations are needed to induce spawning and facilitate larval recruitment. Highlights : Rangia cuneata is an important part of estuarine communities in North America. In labs, the clam spawns after salinity increases and larvae survive in 2–10 salinity. A river saltwater barrier was a natural experiment, testing clam's reproduction needs. The barrier cut off many R. cuneata beds from salinity intrusions, extirpating clams. Salinity intrusions in the Neches River, Texas, were linked with clam age cohorts.